Pengaruh Pupuk Organik Terhadap Pertumbuhan Tanaman dan Kualitas Tanah - Tiesland Zebua; Septin Melindra Gulo; Selvian Suriani Gulo (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
One alternative to increase plant growth and improve soil quality sustainably is organic fertilizer. Based on previous studies, this study discusses how organic fertilizer affects plant growth and soil quality. The results of the study indicate that organic fertilizer can increase plant growth by providing nutrients gradually and supporting the activity of soil microorganisms responsible for decomposing organic matter. The use of organic fertilizers has also been shown to improve soil structure, increase water retention capacity, and enrich it. However, there are several obstacles when using organic fertilizers, such as longer decomposition times and inconsistent nutrient levels. Therefore, efforts to optimize the use of organic fertilizers must be carried out continuously to increase their capacity to support sustainable agriculture.